Does Gender Inclusivity Strengthen the ESG-Financial Performance Nexus? Evidence from Indonesian Public Companies - Cynthia Stephani Pardosi; Riki Martusa; Meythi Meythi; Rapina Rapina (Politeknik Ganesha Medan, 2026)
The foundation for this study is provided by the growing number of organizations using ESG, the emphasis on sustainability, and the gender inclusivity in governance issue. Using Gender Inclusivity in Governance (GIG) as a moderating variable, this study investigates the relationship between firm financial performance and Environment, Social, and Governance (ESG) performance scores. This study population consists of 948 businesses listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, based on data from Refinitiv Eikon. Purposive sampling was used to pick the sample, and 44 companies that revealed their ESG scores during that time were selected. According to the study's use of Moderated Regression Analysis (MRA), there is a favorable correlation between ESG scores and corporate financial performance. The association between ESG scores and financial performance, however, is not significantly moderated by the Gender Inclusivity in Governance (GIG). Given that other businesses are seen to be able to improve their financial performance and investor reputation, these findings can be used as guideline for stakeholders to prioritize ESG. The findings of this study will serve as a foundation for further research into additional factors that affect the financial performance of firms and their ESG rankings. This study contributes to ESG literature in emerging markets by providing empirical evidence that gender inclusivity in governance does not necessarily strengthen the ESG–financial performance relationship in Indonesia, highlighting the presence of symbolic governance practices.